Pengaruh Motivasi Kerja dan Kompensasi Terhadap Disiplin Kerja Karyawan pada Toko Sumber Elektronik Burau - I Komang Mirawardani; Andi Mustika Amin; Rezky Amalia Hamka; Agung Widhi Kurniawan; Muhammad Ilham Wardhana Haerudin (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study aims to determine the effect of work motivation and compensation on employee work discipline. This research is quantitative research with a descriptive approach and multiple linear regression analysis. Data collection techniques with observation, interviews, questionnaires, and documentation. The population in this study were 44 people, who also became the sample in this study with the sampling technique using saturated sampling. The data analysis technique used is multiple linear regression analysis using SPSS 26 software, to test the effect of work motivation and compensation variables on work discipline. The results of this study indicate that work motivation and compensation have a positive and significant effect on employee work discipline, partially and simultaneously. This study shows that the better the work motivation and compensation, the more employee discipline increases at the Burau Electronic Source Store.